Force Control Theory and Method of Human Load Carrying Exoskeleton Suit - Yang, Zhiyong; Gu, Wenjin; Zhang, Jing.; Gui, Lihua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book reports on the latest advances in concepts and further development of principal component analysis (PCA), discussing in detail a number of open problems related to dimensional reduction techniques and their extensions. It brings together research findings, previously scattered throughout many scientific journal papers worldwide, and presents them in a methodologically unified form. Offering vital insights into the subject matter in self-contained chapters that balance the theory and concrete applications, and focusing on open problems, it is essential reading for all researchers and practitioners with an interest in PCA.
Introduction -- Model of Exoskeleton Suit -- Sensitivity Amplification Control of Exoskeleton Suit -- Direct Force Control of Exoskeleton Suit -- Force Control of Exoskeleton Suit Based on Inner Position Loop -- Impedance Control of Exoskeleton Suit -- Impedance Control of Exoskeleton Suit with Uncertainties -- Exoskeleton Suit$1 (Bs Reference Trajectory Estimated Method Based on Neural Network -- Conclusions.s
Keywords: Control engineering; Robotics; Automation; Biomedical engineering; User interfaces (Computer systems).; Human-computer interaction; Control, Robotics, Automation; Biomedical Engineering and Bioengineering; User Interfaces and Human Computer Interaction